2020
DOI: 10.4102/curationis.v43i1.1988
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of student accoucheurs regarding gender inequality in midwifery training at Free State maternal healthcare institutions

Abstract: This study explored and described the perceptions of student accoucheurs regarding gender inequality in midwifery training at the Free State maternal healthcare institutions.Method: An explorative and descriptive qualitative research design was undertaken. There were 40 student accoucheurs that formed 10 focus group discussions. Each focus group discussion had four participants. Tesch's eight-steps of data analysis was used to analyse data.Results: Three major themes emerged during data analysis: meeting the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…It was reported that male students in the midwifery training course experienced gender discrimination during clinical practice. Such gender inequity in nursing education could be overcome through policy revision or curriculum development (Madlala et al, 2021). To improve gender equity in nursing education, mentoring programs for various genders are needed, and the faculty's role is important (Petges & Sabio, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that male students in the midwifery training course experienced gender discrimination during clinical practice. Such gender inequity in nursing education could be overcome through policy revision or curriculum development (Madlala et al, 2021). To improve gender equity in nursing education, mentoring programs for various genders are needed, and the faculty's role is important (Petges & Sabio, 2020).…”
Section: Introductionmentioning
confidence: 99%